The Quality of Official Statistical Information: Approaches and International Practices of Evaluation - Zaiets, S. V. (Statistics of Ukraine, 2020)
The article describes the role of statistics in the economic and social policy setting, the development of public and private sector, and international relations. It is noted that the results of a global assessment of the domestic statistical system indicate that European standards for the quality of statistical information are used in official statistics bodies. At the same time, it is pointed out that the domestic statistical activities face unresolved problems associated with a significant burden on respondents, poor quality of primary data, etc. The methodological foundations and practical issues of monitoring the statistical potential of national statistical systems through the prism of the quality of statistical information production processes proposed by the Partnership in Statistics for Development in the 21st Century are investigated. There are 14 tools for assessing the statistical potential used in the international statistical practice for measuring and evaluating various aspects of national statistical data, including the performance of statistical institutions and the quality of their results. A multidimensional statistical potential indicator (SCI) of the World Bank is considered, which diagnostic framework evaluates the statistical methodology, data source, frequency and timeliness of the publication of the indicators reflecting the production of statistical information in a country, which are harmonized with individual global indicators of the SDG. The dynamics of the statistical potential of the national statistical system of Ukraine among 140 developing countries that borrow funds from the International Bank for Reconstruction and Development are analyzed. It is shown that the decreasing level of the statistical potential in Ukraine is associated with the following components: data sources, frequency and timeliness. To enhance the performance and strengthen the institutional capacity of the existing statistical system, it is proposed to take account of the indicators used for the assessment and monitoring of statistical potential in the methodological and practical activities of official statistics bodies. The need to improve quality, accessibility and comparability of the official statistical information is justified, and respective measures are proposed.